Ecological and intercultural citizenship in the primary English as a foreign language (EFL) classroom: An online project in Argentina - Porto, Melina (2015)
This article describes an online intercultural citizenship project concerning the environment in the primary English-language classroom carried out in 2013/2014 between Argentina and Denmark. It is part of a network of projects coordinated by Michael Byram that involves teachers and researchers in Europe, the US and East Asia. The project is framed within the theory of intercultural citizenship in the foreign-language classroom and it is the only study set in the primary school context. Furthermore, developments in Latin America in this field are scarce and the study intends to fill an empirical gap. Although the comparative perspective is ingrained in the project, the article describes mainly the Argentinian standpoint. At the same time, and more generally (beyond language education), it will be argued, and shown, that the project can also be framed within the notion of ecological citizenship, understood as a new form of citizenship that presents new challenges to educators. While the notion of citizenship in formal education usually assumes nationalist and patriotic mindsets, in this project ecological citizenship offers a new framework that introduces an international, transnational or global perspective. Furthermore, citizenship education tends to be reserved to secondary civics and social studies classrooms and in this sense the focus on the primary school context and on the foreign-language classroom is innovative in this project.